The European Union as a global actor addressing the challenge of contested states - Χυτοπούλου, Ελένη (Πανεπιστήμιο Πελοποννήσου, 2020)
The respect of state sovereignty and the non-interference in domestic affairs of third countries is a guarantee of avoiding conflicts between neighboring countries. However, in the course of history, through wars, borders have dramatically changed, and new entities have emerged, some of which retained their independence while others were annexed to stronger states. Nowadays, there are 193 states recognized by the United Nations and 16 unrecognized states. A considerable number of entities with internationally contested sovereignty are located in the broader EU neighborhood and emerged from the breakup of Yugoslavia and the dissolution of the USSR. Krasner, who introduced the concept of problematic sovereignty, considers that the term sovereignty is linked to the existence of autonomous local government structures, the exercise of effective control on the national territory, the ability to control cross-border activities, and international legal recognition. When one or more features sovereignty is missing it is assumed that sovereignty is problematic. Therefore, the notion of contested statehood encompasses not only the lack of international recognition but also the capacity of the states to exercise authority and control over the whole or part of their territory. As a general rule, the international community confronts, the creation of new states, with distrust and caution, perceiving them as a potential challenge to the international order, especially in those cases with increased geopolitical interest The research examines how much differentiated and efficient is the EU’s approach to concerns the challenges of the contested statehood. The present dissertation examines the EU’s policy towards Kosovo and Georgia in the period 1997-2017. Kosovo, which proclaimed itself an independent state in 2008, faces external contested sovereignty. While Georgia, which has been a member of the UN since 1991, faces internal contested sovereignty over its sovereignty due to the secession of Abkhazia and South Ossetia. The EU supports both countries in consolidating peace and in building a modern state with political and economic means. However, the EU has adapted its interventions to the realities and conditions prevailing in each country. Kosovo has the prospect of becoming a member of the EU. Georgia is a country of Eastern European neighbors without the prospect of joining the EU. As a general appreciation, the EU has helped not only in the reform of both countries but has also helped with its diplomatic activities to mitigate tension, to avoid warfare, and to engage in dialogue among the opposing parties. In conclusion and despite the limitations imposed by geopolitics, the EU has succeeded in strengthening its credibility as a significant global player by constructively intervening in conflict resolution and restoration of peace.
Keywords: Κοσσυφοπέδιο (Δημοκρατία)--Πολιτική και διακυβέρνηση; Ευρωπαϊκή Ένωση, Χώρες της--Εξωτερικές σχέσεις; Συγκρούσεις, Διαχείριση των; Ειρήνη; Ευρωπαϊκή Ένωση; Κοσσυφοπέδιο; Γεωργία; Γεωπολιτική